Effect of the DGAT1 K232A mutation and breed on milk traits in cattle populations of Ethiopia - Samuel, Behailu; Dadi, Hailu; Dinka, Hunduma (Frontiers in Animal Science, 2023)
Non conservative K232A substitution has been reported to explain variation in milk traits in diacylglycerol acyl-CoA acyltransferase 1 (DGAT1) gene. The objective of this study was to estimate the allele and genotype frequency and test associations between K232A variants and milk yield and composition in cattle populations of Ethiopia. Blood and milk samples were collected for genomic DNA extraction and milk components analyses, respectively, from ninety-two randomly selected five breeds of Ethiopia. Gene specific primers were used to amplify 278bp of DGAT1 exon-8 region. Allele and genotype frequency were calculated using Power Marker and GLM procedure of SAS software was used to test the associations of detected genetic variation with milk traits. Boran * HF crosses produced higher daily milk yield than the others (p < 0.05) and Boran and Begait breeds produced milk with higher fat and protein content (p< 0.05),whereas Horro presented higher content of milk lactose than the studied breeds (p< 0.05). Allele K and A and genotypes AA, KA and KK were detected. The frequency of K232 was ranged from (0.50 in Boran * HF cross to 0.97 in Horro) populations. The KK and KA genotypic frequencies observed ranged from 0.50-0.94 and 0.03-0.50 in the zebu populations, respectively. The AA genotype produced more milk in Boran * HF crosses whereas, KA genotype produced more milk in the zebu populations (p<0.05). The fat and lactose content values of KA genotypes were lesser than the KK genotypes in all the genetic groups (p < 0.05). Substitution effect of one copy of k allele leads to significant (p<0.05) increase of fat content up to 0.81% and decrease of daily milk yield and lactose content upto 3L and 0.58% in the sampled populations, respectively. The association study confirmed that DGAT1 K232A marker had significant effects on daily milk yield, milk fat and lactose content in the investigated cattle. These results suggested that DGAT1 K232A marker may be utilized to accelerate future molecular breeding of dairy cattle in tropical zebu and their crossbreds after validation in larger population.